2017
DOI: 10.12968/bjcn.2017.22.sup10.s16
|View full text |Cite
|
Sign up to set email alerts
|

How is lymphofluoroscopy mapping altering lymphoedema management?

Abstract: Lymphoedema management has evolved over many decades, but the core components of treatment remain largely unaltered, such as skin care, compression and self-lymphatic drainage. Near-infrared fluorescence lymphatic imaging (NIRFLI) offers an opportunity to enhance patient outcomes by evaluating and increasing the effectiveness of these treatment options. This is relevant when we consider the impact of this chronic condition and its endemic proportions ( Mortimer, 2014 ), while Moffatt et al (2017) suggests it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…A number of commentary articles described the proposed benefit of ICG lymphography to lymphedema therapy planning and surgical management. For example, Wigg and Cooper105 used ICG lymphography for early lymphedema detection and development of an ICG-guided manual lymphatic drainage technique. Rockson106 noted use of ICG lymphography to assess the patient's lymphatic architecture as clinically useful in early lymphedema diagnosis, informing lymphatic surgery, along with its potential for personalized conservative therapy.…”
Section: Resultsmentioning
confidence: 99%
“…A number of commentary articles described the proposed benefit of ICG lymphography to lymphedema therapy planning and surgical management. For example, Wigg and Cooper105 used ICG lymphography for early lymphedema detection and development of an ICG-guided manual lymphatic drainage technique. Rockson106 noted use of ICG lymphography to assess the patient's lymphatic architecture as clinically useful in early lymphedema diagnosis, informing lymphatic surgery, along with its potential for personalized conservative therapy.…”
Section: Resultsmentioning
confidence: 99%
“…In general, there is a lack of consensus and evidence base to support effective dose, frequency and intensity of CDT, and indeed any alternative interventions [24]. Although there have been several studies purporting MLD or CDT as an effective treatment for HNL identified within Tyker et al systematic review [21,23,26,[28][29][30]32,33,34,37], there are no completed published RCTs examining this topic and the validity of these results is compromised due to methodological inconsistencies, including a lack of blinding of outcome assessment, variations in selection criteria including oncological history across case series, and principle investigators performing outcome measures [31]. The largest of these studies by Smith and Lewin in 2010 [9 && ] failed to identify why only 733 out of the 1202 participants received treatment, and yielded two unmatched cohorts of home programme and outpatient treatment groups.…”
Section: Part 3: Complete Decongestive Therapy As An Intervention For...mentioning
confidence: 99%
“…Most commonly, techniques developed by Foldi, Vodder and Casley-Smith have traditionally been used. Fluoroscopy-guided MLD (FG-MLD) was developed using an adapted Casley-Smith technique of MLD based on mapping of functional lymphatics using real-time Lympho-Fluroscopy imaging [34]. FG-MLD identifies functional and nonfunctional lymphatics, which allows for more targeted drainage pathways.…”
Section: Part 3: Complete Decongestive Therapy As An Intervention For...mentioning
confidence: 99%
“…The emergence of techniques such as near-infrared fluorescence imaging (NIRFI) allows for the individual mapping of superficial lymphatics in those with or at risk of lymphoedema, and is being sought by patients to enhance self-management and individualised care (Wigg and Cooper, 2017). Patients in two of the three case studies mentioned below have received individual mapping of the lymphatic drainage routes at LymphVision, the only private mapping clinic in the UK.…”
Section: Psychological Supportmentioning
confidence: 99%